CULTURALLY-SENSITIVE PSYCHIATRIC NURSING CARE: AN IMPORTANT PRELIMINARY INTERVENTION IN COMMUNITY-BASED ACUTE CARE SETTINGS - Randy Ian Ferenal Gallego (The Indonesian Journal of Public Health, 2020)
ABSTRACKPsychiatric nursing care is an indispensable aspect of the total health care services provided by nurses in both the acute and chronic care settings. This study investigated the extent of preliminary clinical nursing care provided by registered nurses in dealing with clients who have unique psycho-behavioral needs. It further looked into the relationship between the nurses’ socio-economic profile including their ethnic affiliation and the acute care services offered to patients admitted in the regular hospital, non-psychiatric healthcare settings. It used a descriptive-correlational design through a validated and reliability-tested instrument responded by 113 staff nurses from six hospitals around Lanao del Sur. It involved the statistical analysis of data using frequency, weighted mean, and Pearson correlation. The findings show that the nurse-respondents of the selected hospitals in Lanao del Sur generally considers the extent of implementation of the six nursing care areas (counseling, milieu therapy, self-care activities, psychobiologic interventions & health-teachings, case management, health promotion and maintenance) as frequently done or as generally emphasized in about 75% of the time in their respective clinical areas.  When tested at 0.05 level of significance, the p-value obtained was less than the critical value (p=0.00-0.006) revealing that the ethnic affiliation of nurses was significantly correlated to the health promotion and maintenance care that they provide to clients with psycho-behavioral pathologies. Therefore, nurses serving in acute clinical settings need to possess a significant amount of competency in psychiatric care to be able to render preliminary interventions despite non-specialist background. Nurses also have to be cognizant of the cultural history and background of the clients being served even at the preliminary phase of the nurse-patient interaction and accommodate them with nursing interventions based on transcultural competence.Keywords: Culturally-sensitive psychiatric care, psycho-behavioral pathologies, preliminary psychiatric interventions, psychiatric care in acute settings